Fire resistance of engineered cementitious composite - Ng, Wee Feng (2017)
High strength engineered cementitious composite (HSECC) is a new material created through the combination of high strength concrete and normal engineered cementitious composite (NECC). The alteration has shown improvement to the properties of NECC. However, there is hardly any data on the behaviour of HSECC after exposure to elevated temperatures. Therefore, to examine the fire performance of HSECC, uniaxial compression test was conducted on HSECC and NECC after heating for comparison. The residual compressive properties of the heated specimens were examined in this study. Upon observation, it is gathered that HSECC is prone to shrinkage and surface cracking after exposure to temperature above 400°C. Furthermore, although HSECC specimen exhibited a higher compressive strength of 120 MPa at ambient temperature, it lacks the ability to retain its compressive strength and stiffness after heating as compared to NECC. Lastly, it is deduced that steel fibres are able to overcome abrupt failures of specimens after the melting of either PE or PVA fibres. Note that in the discussion of this study, NECC includes NECC-1 and NECC-2, and ECC includes both HSECC and NECC.